RANCANG BANGUN GAME EDUKASI PENGENALAN TOKOH PAHLAWAN INDONESIA MENGGUNAKAN METODE FISHER-YATES SHUFFLE BERBASIS ANDROID - Saiful Bachri , Ahmad; Mashuri , Chamdan; Kristianto , Hery (Inovate, 2023)
As an Indonesian citizen, the author would like to express his gratitude to the heroes who have perseveringly fought for Indonesia's independence and sacrificed everything for the freedom of the homeland. Indonesian heroes are individuals who heroically fight against the colonists who seek to control the territory of Indonesia. Therefore, a strategy is needed for children and adolescents in today’s world to develop a sense of patriotism and love of the homeland. This educational game is designed to add knowledge about Indonesian heroes and the short history of hero fighting. This educational game uses the Fisher-Yates Shuffle method, which works by tracking pieces of a puzzle with unpredictable outcomes and sequences that cannot produce the same numbers when played again. The aim of this research is to build an Android-based educational game to introduce Indonesian heroes, provide education while playing, and make it easily accessible via smartphones. After testing, this Indonesian hero character recognition educational game can help society, especially children, introduce hero characters with a percentage acquisition rate of 83.1%. Keywords: Educational Game, Indonesian Heroes, Fisher-Yates Shuffle.